2021
DOI: 10.22271/fish.2021.v9.i1e.2423
|View full text |Cite
|
Sign up to set email alerts
|

Suckermouth armoured catfish (Pterygoplichthys spp.) menace in freshwater aquaculture and natural aquatic systems in Andhra Pradesh, India

Abstract: Suckermouth armoured catfish (Pterygoplichthys spp.) which is popularly called "Devil fish" in Andhra Pradesh, was recorded in 93.33% of fish ponds out of 600 ha surveyed in Krishna and West Godavari districts including mesohaline ponds wherein salinity ranges from 2 to 20‰. Pterygoplichthys spp. have ranged from 150 to 600 kg/ha that accounts to 2.01-7.50% of total biomass of fish harvested in aquaculture ponds leading to escalation of feed conversion ratio by 25.76%. Consequently, carp production has diminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…For example, Mendoza et al (2007) reported that armored catfish replaced 70-80 % of the fish caught in the El Infiernillo reservoir in Mexico. There is consistent evidence from fishers' reports, analysis of commercial catch, and experimental studies that demonstrate the decrease of native species biomass caused by armored catfish abundance (Hoover et al 2004, Chaichana & Jongphadungkiet 2012, Barba-Macías et al 2017, Suresh et al 2019, Elfidasari et al 2020, Seshagiri et al 2021).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, Mendoza et al (2007) reported that armored catfish replaced 70-80 % of the fish caught in the El Infiernillo reservoir in Mexico. There is consistent evidence from fishers' reports, analysis of commercial catch, and experimental studies that demonstrate the decrease of native species biomass caused by armored catfish abundance (Hoover et al 2004, Chaichana & Jongphadungkiet 2012, Barba-Macías et al 2017, Suresh et al 2019, Elfidasari et al 2020, Seshagiri et al 2021).…”
Section: Discussionmentioning
confidence: 78%
“…In the RNUMM, it is difficult to estimate the economic loss due to armored catfish catch, given the lack of specific studies assessing the quantitative impact on the fisheries; however, fishermen state that on occasions, when many armored catfish are caught, the losses are significant, due to damage of fishing gears, increased effort to remove fish, and reduced capture of valuable species. For example, in Asia, fishers lose 4.5% of their salary to fixing damaged nets caused by armored catfish (Seshagiri et al 2021). In the RNUMM, the most significant loss occurs when the entire net cloth breaks.…”
Section: Discussionmentioning
confidence: 99%
“…Using mesocosm-based approach, several studies have shown that Amazon sailfin catfish negatively impacted the growth of fingerling rohu [fingerling defined in terms of total length (TL, from snout to tip of caudal fin) of <15 cm, Munilkumar and Nandeesha, 2007], when both the species were reared together under similar experimental conditions (Parvez et al, 2023; Mallick et al, 2023). However, the catfish had no significant impact on different abiotic (water quality and soil C/N profiles) and biotic (zoo- and phytoplankton abundance) measures of the given experimental condition (Seshagiri et al, 2021; Parvez et al, 2023; Mallick et al, 2023). Based on the findings, the studies have speculated that the observed negative impact on rohu fingerlings can be mediated via feeding competitions with the catfish (Mallick et al, 2023), and thus, warrants further investigations.…”
Section: Introductionmentioning
confidence: 92%
“…In this paper, we aim to understand competitive interactions in the context of feeding between two freshwater fish species, the Amazon sailfin catfish and rohu, that have been reported to co-occur in different countries across Asia. The Amazon sailfin catfish is native to the Amazon basin, and has been tagged as one of the invasive species in several countries, Mexico (Wakida-Kusunoki et al, 2007), Florida (Ludlow and Walsh, 1991), Texas (Edward, 2001), Malaysia (Saba et al, 2020), Iraq (Qasim and Jawad, 2022), Vietnam (Levin et al, 2008), Philippines (Jumawan et al, 2011), Sri Lanka (Herath et al, 2020), Italy (Piria et al, 2018), Bangladesh (Hossain et al, 2018), and the Indian freshwaters (Bijukumar et al, 2015; Rao and Sunchu, 2017; Hussan et al, 2019; Das et al, 2020; Seshagiri et al, 2021, Mallick et al, 2023). Amazon sailfin catfish is a benthic forager with hard armor and spines, belonging to the Loriicariidae family of catfish, which are considered to be aggressive and territorial (Hossain et al, 2018; Umar and Ramayani, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation